Evolução microestrutural e comportamento mecânico de uma liga Zn-Al hipoeutética com adições de Cu e Mg submetida a forjamento multidirecional - Nayara Aparecida Neres da Silva (2021)
Ultrafine-grained Zn-Al alloys have been produced by different severe plastic deformation (SPD) techniques to improve its superplastic properties, which are favored by grain refinement and the increase in the percentage of high angle grain boundaries. In this context, the present research evaluated of microstructural evolution and mechanical behavior of a hypoeutectic Zn-3,8%Al-2,3%Cu-0,4%Mg alloy, commercially known as Zamak 8, processed by up to 23 cycles of room-temperature multi-directional forging (MDF) with strain amplitude of ~30%; MDF is a simple SPD technique and has several advantages when compared to other techniques. The microstructural characterization was conducted by optical microscopy (OM), scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis, while the mechanical behavior was evaluated by hardness test, compression tests with changes in strain rate and microtensile tests. Experiments were performed to examine the flow behavior and microstructural evolution in a Zn–Al–Cu–Mg alloy processed by up to 23 cycles of multi-directional forging (MDF). After a total strain (ε) of ~20.7 the grain sizes in the primary η-Zn, eutectic and eutectoid components were reduced to ~0.25, 0.4 and 0.3 μm, respectively, starting from the initial grain size of up to 53 μm. The metal exhibits profuse shear banding and twinning and undergoes work hardening in the 1st MDF cycle. Further straining up to ε ≈ 7 promotes significant grain refinement in η-Zn phase together with strain softening due to occurrence of grain boundary sliding. Afterwards, the plastic flow occurs under a constant stress and flow softening is again prevalent for ε > 12. The individual components in the Zn–Al hypoeutectic alloy display different hardening kinetics and grain refinement such that the microstructural changes are first observed in the primary η-Zn areas and subsequently in the eutectoid and eutectic domains. Based on the average hardness in each component, the rule of mixtures was used to estimate the overall material strength after MDF. Although the results show similar trends to those obtained experimentally, it is observed that the rule of mixtures overestimates the flow stresses compared with the in-situ stress-strain curve. This undermines the hypothesis of iso-strain and suggests that deformation concentrates in the weaker areas in the flow softening stages of MDF processing.